The Effect of Corporate Governance on Firm Value of Listed Firms in China - Cao, Xiaowen (2021)
The study’s aim was to investigate the impact that corporate governance poses upon the firm value of the Chinese listed firms in the stock exchange markets. The structures of the owners and the board were used as proxies of corporate governance. Under ownership structure, the study focused on institutional ownership, ownership concentration, and managerial ownership. Under the board structure, this study adopted board size, independence, as well as gender diversity as indicators. The study used data that was collected for the period 2015-2020 and analysed this data using descriptive statistics, correlation, and regression analysis. This considered a random sample of 2,570 firms with 15,420 observations over six years. The findings of the study showed that institutional ownership significantly and positively influences the value of listed companies in China. Managerial ownership was found to pose no impact on value, while ownership concentration was found to negatively influence Chinese listed firms’ value. This study further established that board independence and size generate a significant positive effect on firm value. However, it was found that board gender diversity in Chinese generates no significant impact. This study recommends that the listed firms in China enhance board size and independence to enhance firm value. However, a larger board size should reflect diverse skills set and experience pertinent to driving firm value. Institutional ownership should be encouraged, especially that institutional investors come with knowledge and experience critical in guiding investment and risk management decisions.